Peningkatan Kompetensi Supervisi Akademik Pengawas PAI di Kabupaten Kapuas - Bidin; Abdul Halim Rais (AL-IBNOR, 2024)
Academic supervision is professional assistance provided by supervisors to teachers to improve their competence so that they can develop a higher-quality learning process. The purpose of this writing is to explain how the workshop was carried out to improve the competence of academic supervision by supervisors. This workshop uses an adult learning approach (andragogy) with a learning model oriented towards higher-order thinking skills (Order Thinking Skills abbreviated as HOTS) which provides space for School Supervisor participants to share the best insights, knowledge, understanding, and experiences. HOTS includes 4C (critical thinking, creativity, collaboration, communication), literacy, and strengthening character education which emphasizes essential themes that improve school supervisor performance indicators. With the pattern 1) On the Job Training I (OJT I), 2) In Service Training (IST) 3) On the Job Training II (OJT II). The results obtained from this workshop were to increase the academic supervision competence of PAI supervisors who took part in this activity.